Titanium alloy lattice structure heat-quench integrated process and device

CN121732836BActive Publication Date: 2026-10-20ZHONGBEI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610238888.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-28
Publication Date
2026-10-20
Estimated Expiration
2046-02-28

AI Technical Summary

Technical Problem

[0003]然而,现有的EBM技术存在以下问题:1.后处理工序分离:EBM成型后需要进行单独的热处理工序,增加了生产周期和成本;2.淬透性控制困难:对于不同杆径的点阵结构,难以实现均匀的淬透效果;3.组织性能不匹配:单一冷却参数无法满足不同杆径结构的组织优化需求;4.工件转移风险:将高温成型的EBM工件转移到专用热处理设备的过程中,存在氧化、变形和污染风险

Benefits of technology

[0017]本申请提出了一种钛合金点阵结构热-淬一体化工艺及装置,产生了如下有益效果:将EBM成型与液氮淬火处理集成在同一设备中完成,通过液氮气化降低构建室内的真空度和温度,降低了工件氧化风险且提高了效率;利用液氮淬火快速冷却,能促进钛合金中细小的α'马氏体形成,还能在钛合金表面形成氮化层,提高了工件的强度、硬度和耐磨性;通过系统研究不同杆径钛合金点阵结构与液氮流量的匹配关系,利用可控的液氮喷射系统,能实现对淬透性的精确控制,提高了工件质量的一致性和稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121732836B_ABST
    Figure CN121732836B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of metal additive manufacturing, and particularly relates to a titanium alloy dot array structure heat-quench integrated process and device. The process comprises the following steps: under vacuum conditions, using titanium alloy powder to print a titanium alloy dot array structure in a high-energy beam melting equipment; after printing is completed, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow of the liquid nitrogen is controlled to quench the titanium alloy dot array structure. The process integrates EBM forming and liquid nitrogen quenching treatment in the same equipment, reduces the risk of workpiece oxidation and improves the efficiency; the liquid nitrogen quenching rapid cooling can promote the formation of fine alpha prime martensite in the titanium alloy, and can also form a nitriding layer on the surface of the titanium alloy, thereby improving the strength, hardness and wear resistance of the workpiece; the controllable liquid nitrogen spraying system can realize accurate control of the quenching performance, thereby improving the consistency and stability of the workpiece quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of metal additive manufacturing technology, specifically a hot-quenching integrated process and apparatus for titanium alloy lattice structures. Background Technology

[0002] High-energy beam melting (EBM) is an important metal additive manufacturing technology, particularly suitable for fabricating complex lattice structure titanium alloy components commonly used in aerospace and biomedical fields. The EBM process is performed in a vacuum environment, where a high-energy beam scans and melts metal powder, depositing it layer by layer to form a three-dimensional component.

[0003] However, existing EBM technology has the following problems: 1. Separation of post-processing: EBM requires a separate heat treatment process after forming, which increases the production cycle and cost; 2. Difficulty in controlling hardenability: It is difficult to achieve a uniform hardenability effect for lattice structures with different rod diameters; 3. Mismatch between microstructure and properties: A single cooling parameter cannot meet the microstructure optimization requirements of structures with different rod diameters; 4. Workpiece transfer risk: There is a risk of oxidation, deformation and contamination during the process of transferring EBM workpieces formed at high temperature to dedicated heat treatment equipment.

[0004] Especially for complex lattice structures, there is currently a lack of systematic hardenability data to guide process optimization. Liquid nitrogen, as an extremely low temperature cooling medium, has been applied in metal heat treatment, but there are no reports on its integration into EBM processes for integrated manufacturing, or on the systematic study of the hardenability of lattice structures with different rod diameters. Summary of the Invention

[0005] To address the aforementioned issues, the purpose of this application is to provide an integrated hot-quenching process and apparatus for titanium alloy lattice structures. This process, through EBM forming and liquid nitrogen quenching, can precisely control the hardenability of titanium alloy lattice structures with different rod diameters.

[0006] According to a first aspect of this application, this application provides an integrated hot-quenching process for titanium alloy lattice structures, comprising the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. S2. After printing is completed, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of the liquid nitrogen is controlled to quench the titanium alloy lattice structure.

[0007] Furthermore, the titanium alloy powder includes Ti-6Al-4V or Ti-8Al-1Mo-1V.

[0008] Furthermore, step S2 also includes, after printing is completed, when the temperature of the titanium alloy lattice structure drops to 50~100°C below the β transformation temperature, introducing liquid nitrogen into the high-energy beam melting equipment and controlling the flow rate of the liquid nitrogen to quench the titanium alloy lattice structure.

[0009] Furthermore, step S1 also includes laying titanium alloy powder on the substrate of the high-energy beam melting device, and controlling the pressure in the construction chamber of the high-energy beam melting device to not exceed 5 × 10⁻⁶. -3 Pa, the substrate is preheated to 600~700°C and the temperature of the construction chamber is maintained at 650~700°C. The titanium alloy powder is used in the high-energy beam melting equipment to print titanium alloy lattice structures.

[0010] Furthermore, the accelerating voltage during the printing process is 30~60kV, the beam current is 5~20mA, and the scanning speed is 18~30m / s, while the beam current during the preheating process is 30~65mA and the scanning speed is 30~65m / s.

[0011] Furthermore, the layer thickness during the printing process is 55~150μm, and the pass spacing is 5~180μm.

[0012] Furthermore, when the rod diameter of the titanium alloy lattice structure is greater than or equal to 1 mm and less than or equal to 1.5 mm, the flow rate of the liquid nitrogen is controlled to be greater than 10 L / min and less than or equal to 20 L / min. When the diameter of the titanium alloy lattice structure is greater than 1.5 mm and less than or equal to 2 mm, the flow rate of the liquid nitrogen is controlled to be greater than 20 L / min and less than or equal to 30 L / min.

[0013] Furthermore, step S2 also includes introducing liquid nitrogen into the high-energy beam melting device using a multi-nozzle injection system, wherein the flow rate of the liquid nitrogen injected by each nozzle in the multi-nozzle injection system is independently controlled.

[0014] Furthermore, a nitrided layer is formed on the surface of the quenched titanium alloy lattice structure, and the thickness of the nitrided layer is 2~10μm.

[0015] According to a second aspect of this application, this application provides a heat-quenching integrated device for titanium alloy lattice structures, used to realize the heat-quenching integrated process for titanium alloy lattice structures as described in any of the above claims. The device is a high-energy beam melting device, comprising: a construction chamber and a liquid nitrogen spraying system. The liquid nitrogen injection system includes a liquid nitrogen storage unit, a multi-nozzle injection system, a flow regulation system, and a temperature monitoring system; The multi-nozzle spraying system includes a nozzle, the temperature monitoring system includes a detection probe, and the nozzle and the detection probe are disposed inside the construction chamber; The flow regulation system is located between the liquid nitrogen storage unit and the multi-nozzle injection system, and is connected to the flow regulation system and the multi-nozzle injection system respectively through a delivery pipeline; The liquid nitrogen storage unit, the multi-nozzle injection system, the flow regulation system, and the temperature monitoring system are all connected to a computer and can be controlled by the computer.

[0016] Furthermore, the flow regulation system controls the flow rate of liquid nitrogen ejected by the multi-nozzle injection system to be 5~30L / min, with a control accuracy of ±0.5L / min.

[0017] This application proposes an integrated hot-quenching process and apparatus for titanium alloy lattice structures, which produces the following beneficial effects: EBM forming and liquid nitrogen quenching are integrated into the same equipment; the vacuum and temperature in the forming chamber are reduced by liquid nitrogen vaporization, lowering the risk of workpiece oxidation and improving efficiency; rapid cooling using liquid nitrogen quenching promotes the formation of fine α' martensite in the titanium alloy and forms a nitrided layer on the surface, improving the workpiece's strength, hardness, and wear resistance; through systematic research on the matching relationship between titanium alloy lattice structures of different rod diameters and liquid nitrogen flow rate, a controllable liquid nitrogen injection system enables precise control of hardenability, improving the consistency and stability of workpiece quality. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0019] Figure 1 This is a schematic diagram of the liquid nitrogen injection system inside the high-energy beam melting device of this application; Figure 2 These are schematic diagrams of titanium alloy lattice structures with a rod diameter of 1 mm in Examples 1-3; Figure 3 These are schematic diagrams of titanium alloy lattice structures with a rod diameter of 2 mm as shown in Examples 4-6; The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0020] The technical solutions in the embodiments will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0021] According to a first aspect of this application, this application provides an integrated hot-quenching process for titanium alloy lattice structures, comprising the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. Preferably, titanium alloy powder is deposited on the substrate of the high-energy beam melting device, and the pressure in the construction chamber of the high-energy beam melting device is controlled to not exceed 5 × 10⁻⁶. -3 Pa, the substrate is preheated to 600~700℃, the beam current during the preheating process is 30~65mA, the scanning speed is 30~65m / s, and the temperature of the build chamber is maintained at 650~700℃. Titanium alloy lattice structure is printed using titanium alloy powder in a high-energy beam melting device. During the printing process, the acceleration voltage of the high-energy beam is 30~60kV, the beam current is 5~20mA, the scanning speed is 18~30m / s, the layer thickness is 55~150μm, and the pass spacing is 5~180μm; Specifically, the substrate is preheated to any one or a combination of 600℃, 620℃, 640℃, 660℃, 680℃, and 700℃; the beam current during preheating can be any one or a combination of 30mA, 40mA, 50mA, 60mA, and 65mA; the scanning speed can be any one or a combination of 30m / s, 40m / s, 50m / s, 60m / s, and 65m / s; the temperature of the build chamber is maintained at any one or a combination of 650℃, 660℃, 670℃, 680℃, 690℃, and 700℃; and the accelerating voltage during printing can be 30... The voltage range can be any one or any two of kV, 40kV, 50kV, and 60kV; the beam current can be any one or any two of 5mA, 10mA, 15mA, and 20mA; the scan speed can be any one or any two of 18m / s, 21m / s, 24m / s, 27m / s, and 30m / s; the slice thickness can be any one or any two of 55μm, 70μm, 90μm, 110μm, 130μm, and 150μm; and the pass spacing can be any one or any two of 5μm, 50μm, 100μm, 150μm, and 180μm.

[0022] S2. After printing, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of liquid nitrogen is controlled to quench the titanium alloy lattice structure. Specifically, after printing, high-energy beam scanning and heating are stopped, and a small amount of high-temperature nitrogen gas is injected at high speed into the chamber to separate the titanium alloy lattice structure from the titanium alloy powder. When the temperature of the titanium alloy lattice structure drops to 50-100°C below the β-transformation temperature, liquid nitrogen is introduced into the high-energy beam melting equipment. Upon contact with the high-temperature titanium alloy lattice structure, the liquid nitrogen rapidly vaporizes, forming a uniform cooling medium to uniformly cool the titanium alloy lattice structure and simultaneously reduce the vacuum level in the high-energy beam melting equipment. During the process, the flow rate of liquid nitrogen is adjusted to differentiate the control of lattice structures with different rod diameters to achieve precise control of hardenability. If the rod diameter of the titanium alloy lattice structure is greater than or equal to 1 mm and less than or equal to 1.5 mm, the flow rate of liquid nitrogen is controlled accordingly. The flow rate should be greater than 10 L / min and less than or equal to 20 L / min. If the diameter of the rod in the titanium alloy lattice structure is greater than 1.5 mm and less than or equal to 2 mm, the flow rate of liquid nitrogen should be controlled to be greater than 20 L / min and less than or equal to 30 L / min. At the same time, after liquid nitrogen comes into contact with the high-temperature titanium alloy lattice structure, a nitride layer with a thickness of 2~10 μm can be formed on the surface of the titanium alloy. This is because liquid nitrogen decomposes into active nitrogen atoms on the surface of the high-temperature titanium alloy, and the nitrogen atoms diffuse into the surface of the titanium alloy to form nitrides. Generally speaking, the thickness of the nitride layer increases with the increase of liquid nitrogen flow rate and quenching time. Therefore, the thickness of the nitride layer can be controlled by controlling the liquid nitrogen flow rate and quenching time. At the same time, the aluminum element in the titanium alloy can significantly promote the growth of the nitride layer.

[0023] In some embodiments of this application, Ti-6Al-4V (TC4) or Ti-8Al-1Mo-1V (TA11) titanium alloy powders are used to prepare titanium alloy lattice structures with rod diameters of 1 mm or 2 mm. TC4 alloy contains 6 wt% aluminum and 4 wt% vanadium, exhibiting moderate β-phase stability. Complete quenching can be achieved by controlling the liquid nitrogen flow rate at 15-30 L / min, maintaining a cooling rate within the range of 45-65 °C / s. Furthermore, the nitride layer formed on its surface mainly consists of TiN and Ti2N phases, with a relatively thin thickness (2-7 μm) but high hardness. TA11, with its higher aluminum content (8 wt%), improves its α-phase stability. Complete quenching can be achieved by controlling the liquid nitrogen flow rate at 20-30 L / min, maintaining a cooling rate within the range of 50-60 °C / s. Its surface nitride layer mainly consists of TiN, AlN, and complex nitrides, with a significantly increased thickness (8-10 μm) and higher hardness. This is because the higher aluminum content promotes the formation of a thicker AlN reinforcing layer.

[0024] According to a second aspect of this application, this application provides a high-energy beam melting apparatus for realizing the above-mentioned integrated hot-quenching process of titanium alloy lattice structures, comprising: a construction chamber and a... Figure 1The liquid nitrogen injection system shown; The liquid nitrogen injection system includes a liquid nitrogen storage unit, a multi-nozzle injection system, a flow regulation system, and a temperature monitoring system; The multi-nozzle spraying system includes a nozzle, and the temperature monitoring system includes a detection probe, with the nozzle and detection probe located inside the construction chamber; The flow regulation system is located between the liquid nitrogen storage unit and the multi-nozzle injection system, and is connected to the flow regulation system and the multi-nozzle injection system respectively through delivery pipelines; The liquid nitrogen storage unit, multi-nozzle injection system, flow regulation system, and temperature monitoring system are all connected to and can be controlled by a computer.

[0025] Preferably, the flow regulation system controls the flow rate of liquid nitrogen ejected by the multi-nozzle injection system to be 5~30L / min, with a control accuracy of ±0.5L / min; Preferably, the flow rate of liquid nitrogen is controlled in stages according to the diameter of the rod in the titanium alloy lattice structure, including low flow rate, medium flow rate and high flow rate, wherein the low flow rate is greater than or equal to 5 L / min and less than or equal to 10 L / min, the medium flow rate is greater than 10 L / min and less than or equal to 20 L / min, and the high flow rate is greater than 20 L / min and less than or equal to 30 L / min.

[0026] The technical solution of this application will be further described below with reference to specific embodiments.

[0027] Example 1 A heat-quenching integrated process for titanium alloy lattice structures includes the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. The titanium alloy powder used is TC4; the accelerating voltage during the printing process is 50kV, the beam current is 12mA, and the scanning speed is 30m / s; the titanium alloy lattice structure is a cubic lattice with a unit size of 4×4×4mm and a rod diameter of 1.0mm. S2. After printing, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of liquid nitrogen is controlled to quench the titanium alloy lattice structure. The temperature of the titanium alloy lattice structure when liquid nitrogen is introduced is 950℃; the liquid nitrogen flow rate is 8L / min; the liquid nitrogen injection mode is intermittent (5s injection, 5s interval); and the quenching time is 12min. The performance test results of the titanium alloy lattice structure after quenching in this embodiment are as follows: cooling rate is 28~35℃ / s, surface hardness is HV385±15, core hardness is HV355±20, quenching depth is 0.6~0.7mm, quenching rate is 65%, surface nitriding layer thickness is 1~2μm, nitriding layer microhardness is HV650±50, and its microstructure is fine lath α' martensite on the surface and α+β mixed structure in the core.

[0028] Example 2 A heat-quenching integrated process for titanium alloy lattice structures includes the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. The titanium alloy powder used is TC4; the accelerating voltage during the printing process is 50kV, the beam current is 12mA, and the scanning speed is 30m / s; the titanium alloy lattice structure is a cubic lattice with a unit size of 4×4×4mm and a rod diameter of 1.0mm. S2. After printing, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of liquid nitrogen is controlled to quench the titanium alloy lattice structure. The temperature of the titanium alloy lattice structure was 950℃ when liquid nitrogen was introduced; the liquid nitrogen flow rate was 15L / min; the liquid nitrogen injection mode was continuous; and the quenching time was 10min. The performance test results of the titanium alloy lattice structure after quenching in this embodiment are as follows: cooling rate is 45~55℃ / s, surface hardness is HV405±10, core hardness is HV395±12, quenching depth is 0.9~1.0mm, quenching rate is 100%, surface nitriding layer thickness is 2~3μm, nitriding layer microhardness is HV680±40, and its microstructure is a uniform and fine α' martensite structure.

[0029] Example 3 A heat-quenching integrated process for titanium alloy lattice structures includes the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. The titanium alloy powder used is TC4; the accelerating voltage during the printing process is 50kV, the beam current is 12mA, and the scanning speed is 30m / s; the titanium alloy lattice structure is a cubic lattice with a unit size of 4×4×4mm and a rod diameter of 1.0mm. S2. After printing, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of liquid nitrogen is controlled to quench the titanium alloy lattice structure. The temperature of the titanium alloy lattice structure was 950℃ when liquid nitrogen was introduced; the liquid nitrogen flow rate was 25L / min; the liquid nitrogen injection mode was continuous; and the quenching time was 8min. The performance test results of the titanium alloy lattice structure after quenching in this embodiment are as follows: the cooling rate is 65~75℃ / s, the surface hardness is HV420±8, the core hardness is HV410±10, the quenching depth is 1.0mm, the quenching rate is 100%, the surface nitride layer thickness is 4~5μm, the nitride layer microhardness is HV720±30, its microstructure is ultrafine α' martensite, and microcracks appear in some areas.

[0030] Example 4 A heat-quenching integrated process for titanium alloy lattice structures includes the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. The titanium alloy powder used is TC4; the accelerating voltage during the printing process is 50kV, the beam current is 15mA, and the scanning speed is 20m / s; the titanium alloy lattice structure is a cubic lattice with a unit size of 5×5×5mm and a rod diameter of 2.0mm. S2. After printing, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of liquid nitrogen is controlled to quench the titanium alloy lattice structure. The temperature of the titanium alloy lattice structure when liquid nitrogen is introduced is 950℃; the liquid nitrogen flow rate is 10L / min; the liquid nitrogen injection mode is intermittent (8s injection, 4s interval); and the quenching time is 18min. The performance test results of the titanium alloy lattice structure after quenching in this embodiment are as follows: cooling rate is 20~25℃ / s, surface hardness is HV375±18, core hardness is HV325±25, quenching depth is 0.8~1.0mm, quenching rate is 45%, surface nitriding layer thickness is 3~4μm, nitriding layer microhardness is HV620±45, and its microstructure is α' martensite on the surface and coarse α+β structure in the core.

[0031] Example 5 A heat-quenching integrated process for titanium alloy lattice structures includes the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. The titanium alloy powder used is TC4; the accelerating voltage during the printing process is 50kV, the beam current is 15mA, and the scanning speed is 20m / s; the titanium alloy lattice structure is a cubic lattice with a unit size of 5×5×5mm and a rod diameter of 2.0mm. S2. After printing, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of liquid nitrogen is controlled to quench the titanium alloy lattice structure. The temperature of the titanium alloy lattice structure was 950℃ when liquid nitrogen was introduced; the liquid nitrogen flow rate was 18L / min; the liquid nitrogen injection mode was continuous; and the quenching time was 15min. The performance test results of the titanium alloy lattice structure after quenching in this embodiment are as follows: cooling rate is 35~45℃ / s, surface hardness is HV395±12, core hardness is HV380±15, quenching depth is 1.5~1.7mm, quenching rate is 80%, surface nitriding layer thickness is 5~6μm, nitriding layer microhardness is HV670±35, and its microstructure is fine martensite on the surface, mixed structure in the transition zone, and a small amount of untransformed β phase in the core.

[0032] Example 6 A heat-quenching integrated process for titanium alloy lattice structures includes the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. The titanium alloy powder used is TC4; the accelerating voltage during the printing process is 50kV, the beam current is 15mA, and the scanning speed is 20m / s; the titanium alloy lattice structure is a cubic lattice with a unit size of 5×5×5mm and a rod diameter of 2.0mm. S2. After printing, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of liquid nitrogen is controlled to quench the titanium alloy lattice structure. The temperature of the titanium alloy lattice structure was 950℃ when liquid nitrogen was introduced; the liquid nitrogen flow rate was 28L / min; the liquid nitrogen injection mode was continuous; and the quenching time was 12min. The performance test results of the titanium alloy lattice structure after quenching in this embodiment are as follows: cooling rate is 55~65℃ / s, surface hardness is HV415±10, core hardness is HV305±12, quenching depth is 2.0mm, quenching rate is 100%, surface nitride layer thickness is 5~7μm, nitride layer microhardness is HV710±25, and its microstructure is a uniform α' martensite structure with no untransformed structure.

[0033] Example 7 A heat-quenching integrated process for titanium alloy lattice structures includes the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. The titanium alloy powder used is TA11; the accelerating voltage during the printing process is 55kV, the beam current is 14mA, and the scanning speed is 18m / s; the titanium alloy lattice structure is a cubic lattice with a unit size of 5×5×5mm and a rod diameter of 2.0mm. S2. After printing, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of liquid nitrogen is controlled to quench the titanium alloy lattice structure. The temperature of the titanium alloy lattice structure was 1000℃ when liquid nitrogen was introduced; the liquid nitrogen flow rate was 12L / min; the liquid nitrogen injection mode was intermittent (10s injection, 5s interval); and the quenching time was 20min. The performance test results of the titanium alloy lattice structure after quenching in this embodiment are as follows: cooling rate is 25~35℃ / s, surface hardness is HV365±20, core hardness is HV315±28, quenching depth is 0.7~0.9mm, quenching rate is 40%, surface nitriding layer thickness is 6~8μm, nitriding layer microhardness is HV750±40, and its microstructure is α' martensite on the surface and α2+β structure in the core.

[0034] Example 8 A heat-quenching integrated process for titanium alloy lattice structures includes the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. The titanium alloy powder used is TA11; the accelerating voltage during the printing process is 55kV, the beam current is 14mA, and the scanning speed is 18m / s; the titanium alloy lattice structure is a cubic lattice with a unit size of 5×5×5mm and a rod diameter of 2.0mm. S2. After printing, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of liquid nitrogen is controlled to quench the titanium alloy lattice structure. The temperature of the titanium alloy lattice structure was 1000℃ when liquid nitrogen was introduced; the liquid nitrogen flow rate was 22L / min; the liquid nitrogen injection mode was continuous; and the quenching time was 16min. The performance test results of the titanium alloy lattice structure after quenching in this embodiment are as follows: cooling rate is 50~60℃ / s, surface hardness is HV390±15, core hardness is HV375±18, quenching depth is 1.8~2.0mm, quenching rate is 95%, surface nitriding layer thickness is 8~10μm, nitriding layer microhardness is HV820±35, and its microstructure is fine α' martensite with a small amount of α2 phase.

[0035] Example 9 A heat-quenching integrated process for titanium alloy lattice structures includes the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. The titanium alloy powder used is TA11; the accelerating voltage during the printing process is 55kV, the beam current is 14mA, and the scanning speed is 18m / s; the titanium alloy lattice structure is a cubic lattice with a unit size of 5×5×5mm and a rod diameter of 2.0mm. S2. After printing, liquid nitrogen is introduced into the high-energy beam melting equipment, and the flow rate of liquid nitrogen is controlled to quench the titanium alloy lattice structure. The temperature of the titanium alloy lattice structure was 1000℃ when liquid nitrogen was introduced; the liquid nitrogen flow rate was 30L / min; the liquid nitrogen injection mode was continuous; and the quenching time was 14min. The performance test results of the titanium alloy lattice structure after quenching in this embodiment are as follows: cooling rate is 70~80℃ / s, surface hardness is HV410±12, core hardness is HV395±15, quenching depth is 2.0mm, quenching rate is 100%, surface nitride layer thickness is 10~12μm, nitride layer microhardness is HV880±30, its microstructure is ultrafine α' martensite, and microcracks appear in the surface nitride layer.

[0036] Schematic diagrams of the titanium alloy lattice structures prepared in Examples 1-3 of this application are shown below. Figure 2 Schematic diagrams of the titanium alloy lattice structures prepared in Examples 4-6 are shown below. Figure 3 .

[0037] This application proposes an integrated hot-quenching process and apparatus for titanium alloy lattice structures, which produces the following beneficial effects: EBM forming and liquid nitrogen quenching are integrated into the same equipment; the vacuum and temperature in the forming chamber are reduced by liquid nitrogen vaporization, lowering the risk of workpiece oxidation and improving efficiency; rapid cooling using liquid nitrogen quenching promotes the formation of fine α' martensite in the titanium alloy and forms a nitrided layer on the surface, improving the workpiece's strength, hardness, and wear resistance; through systematic research on the matching relationship between titanium alloy lattice structures of different rod diameters and liquid nitrogen flow rate, a controllable liquid nitrogen injection system enables precise control of hardenability, improving the consistency and stability of workpiece quality.

[0038] The above description is only a preferred embodiment of this application and does not limit the patent scope of this application. All equivalent structural transformations made using the content of this application's specification under the inventive concept of this application, or direct / indirect applications in other related technical fields, are included within the patent protection scope of this application.

Claims

1. A heat-quenching integrated process for titanium alloy lattice structures, characterized in that, Includes the following steps: S1. Under vacuum conditions, titanium alloy powder is used to print titanium alloy lattice structures in a high-energy beam melting device. The titanium alloy powder includes Ti-6Al-4V or Ti-8Al-1Mo-1V. S2. After printing is completed, stop high-energy beam scanning and heating, and inject a small amount of high-temperature nitrogen gas at high speed into the build chamber of the high-energy beam melting equipment to separate the titanium alloy lattice structure from the titanium alloy powder. When the temperature of the titanium alloy lattice structure drops to 50~100°C below the β transformation temperature, liquid nitrogen is introduced into the high-energy beam melting equipment. The liquid nitrogen rapidly vaporizes upon contact with the high-temperature titanium alloy lattice structure, forming a uniform cooling medium to uniformly cool the titanium alloy lattice structure, while also reducing the vacuum level in the high-energy beam melting equipment. The flow rate of the liquid nitrogen is controlled to quench the titanium alloy lattice structure. Rapid cooling using liquid nitrogen quenching promotes the formation of fine α' martensite in the titanium alloy and also forms a nitrided layer on the surface of the titanium alloy with a thickness of 2~10μm. When the diameter of the rod in the titanium alloy lattice structure is greater than or equal to 1 mm and less than or equal to 1.5 mm, the flow rate of the liquid nitrogen is controlled to be greater than 10 L / min and less than or equal to 20 L / min. When the diameter of the titanium alloy lattice structure is greater than 1.5 mm and less than or equal to 2 mm, the flow rate of the liquid nitrogen is controlled to be greater than 20 L / min and less than or equal to 30 L / min.

2. The integrated hot-quenching process for titanium alloy lattice structures according to claim 1, characterized in that, Step S1 further includes laying titanium alloy powder on the substrate of the high-energy beam melting device and controlling the pressure in the construction chamber of the high-energy beam melting device to not exceed 5 × 10⁻⁶. -3 Pa, the substrate is preheated to 600~700°C and the temperature of the construction chamber is maintained at 650~700°C. The titanium alloy powder is used in the high-energy beam melting equipment to print titanium alloy lattice structures.

3. The integrated hot-quenching process for titanium alloy lattice structures according to claim 2, characterized in that, The accelerating voltage during the printing process is 30~60kV, the beam current is 5~20mA, and the scanning speed is 18~30m / s. The beam current during the preheating process is 30~65mA, and the scanning speed is 30~65m / s.

4. The integrated hot-quenching process for titanium alloy lattice structures according to claim 1, characterized in that, Step S2 further includes introducing liquid nitrogen into the high-energy beam melting device using a multi-nozzle injection system, wherein the flow rate of the liquid nitrogen injected by each nozzle in the multi-nozzle injection system is independently controlled.

5. A titanium alloy lattice structure integrated hot-quenching device, characterized in that, The apparatus for implementing the integrated hot-quenching process of titanium alloy lattice structure according to any one of claims 1 to 4 is a high-energy beam melting device, comprising: a building chamber and a liquid nitrogen spraying system; The liquid nitrogen injection system includes a liquid nitrogen storage unit, a multi-nozzle injection system, a flow regulation system, and a temperature monitoring system; The multi-nozzle spraying system includes a nozzle, the temperature monitoring system includes a detection probe, and the nozzle and the detection probe are disposed inside the construction chamber; The flow regulation system is located between the liquid nitrogen storage unit and the multi-nozzle injection system, and is connected to the flow regulation system and the multi-nozzle injection system respectively through a delivery pipeline; The liquid nitrogen storage unit, the multi-nozzle injection system, the flow regulation system, and the temperature monitoring system are all connected to a computer and can be controlled by the computer.

6. The integrated hot-quenching device for titanium alloy lattice structure according to claim 5, characterized in that, The flow regulation system controls the flow rate of liquid nitrogen ejected by the multi-nozzle injection system to be 5~30L / min, with a control accuracy of ±0.5L / min.

Citation Information

Patent Citations

  • Heat treatment-liquid nitrogen treatment-cryogenic forging composite forming method for obtaining alpha '+ alpha' biphase martensitic structure titanium alloy

    CN120790811A

  • Electron beam melting wire liquid nitrogen cryogenic additive manufacturing method and system

    CN121131966A